Empathy-Driven MVP Design For Digital Circumcision Services In Indonesia - Bayu Kelana; Albert Sembiring (Indonesian Journal of Innovation Multidisipliner Research, 2026)
Independent circumcision services are widely practised across Indonesia, particularly in areas with limited access to formal healthcare facilities; however, digital innovation in this sector remains limited despite national policies promoting electronic medical records. This study aims to design a Minimum Viable Product (MVP) for digital circumcision services using an empathy-driven approach within the Design Science Research (DSR) paradigm. An exploratory qualitative method was employed through in-depth interviews with four independent circumcision operators from different regions. Data were analysed using a six-element empathy map framework and cross-informant qualitative analysis to identify user needs. The results identify six core needs among operators: structured digital communication, automated administration and scheduling, home care support, digital reputation management, continuous education, and socio-spiritual integration. Based on these findings, five core MVP features were developed as the DSR artefact: a patient monitoring dashboard, WhatsApp API integration, a testimonial and portfolio module, a collaboration and education space, and a location-based service catalogue. The study contributes to digital health and information systems research by providing an empirically grounded MVP design that aligns technological functionality with the social and cultural context of community-based healthcare services.